O compositor na sala de aula: sonoridades contemporâneas para educação musical - Borges, Alvaro Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This thesis was developed to lessen the absence of the repertoire of contemporary, experimental and electroacoustic music in the school environment. Contemplated by composer Guy Reibel, this finding, caused by a lack of communicability of some unfamiliar code, was verified through observations and analyses of the “School Music Program” at the City of Pouso Alegre - MG. This program is a demonstration of social and political opportunity, being that since 2005 it provides access to music education in regular schools by a structured process. However it doesn’t address the contemporary repertoire and pedagogical techniques that embrace it. We don’t want to reduce the merits or the relevance of Minas Gerais public policy, which has a differentiated performance if compared to other states in Brazil regarding the teaching of music. The study sought ways to expand the actions already consolidated for greater coverage on performances in the schools. Preliminary observations were focused on some aspects: the origin of the program as a result of public policies and description of its structures and its relationship with the conservatories programs “School Music Program”, as well as its scope in municipal schools. Subsequently, bridges were built to approach the educators of the program to the educational musical repertoire that involves alternative ways to listen and make music following some contributions of the composers-educators from the mid twentieth century, namely Murray Schafer, Guy Reibel, John Paynter, Boris and George Porena Self and others. The structural development process of this research was the educational experiences analysis developed through meetings with the program educators and the researcher, called “Training Workshops”, as well as an analysis of the direct work of the educators in the schools with their students. The main purpose of this procedure was to expand the teach ...

Esta tese foi ensejada pela constatação da ausência de repertório da música contemporânea, experimental e eletroacústica no ambiente escolar. Esta constatação, especulada pelo compositor Guy Reibel, tendo como causa a pouca comunicabilidade por ter um código pouco conhecido, pôde ser verificada pela observação e análise de ações do Programa “Música na Escola”, do Município de Pouso Alegre – MG. Este Programa é uma demonstração de comprometimento político e social, por ser uma instituição que, desde 2005, dá acesso ao ensino de música na escola regular de forma estruturada, porém sem contemplar o repertório musical contemporâneo ou técnicas pedagógicas que o acolham. Não se excluem os méritos desta política pública, que dá relevância ao Estado de Minas Gerais, por ter este uma atuação diferenciada em relação a outros Estados da União, no que se refere ao ensino da música. Esta pesquisa buscou formas de ampliar suas ações já consolidadas para uma maior abrangência na atuação docente em suas escolas e abrir espaço a novas abordagens. As observações preliminares se concentraram nos seguintes aspectos: a origem do Programa como resultado de ação de políticas públicas, descrição de suas estruturas, estabelecimento de relações com os Projetos “Música na Escola” dos conservatórios mineiros, bem como o reconhecimento de sua abrangência na Rede Municipal de Ensino. Buscou-se, posteriormente, criar pontes de aproximação entre os educadores do Programa e o repertório musical e didático que envolve formas alternativas de ouvir e fazer música, reportando-se às propostas dos compositoreseducadores da metade do século XX, ou seja, Murray Schafer, Guy Reibel, John Paynter, Boris Porena e George Self, entre outros. Este processo de desenvolvimento estrutural da pesquisa ocorreu pela análise das estruturas pedagógicas vivenciadas em reuniões dos ...
Keywords: Musica - Instrução e estudo; Composição (Musica); Música - Séc. XX; Music Instruction and study